Locked Rotor Fault Analysis in Dual Rotor Wound Field Flux Switching Generator for Counter-Rotating Wind Turbine Application - Wasiq Ullah; Faisal Khan; Udochukwu B. Akuru; Mehroz Fatima (Machines)
In this paper, the performance of the Independent Dual Rotor Wound Field Flux Switching Generator (IDRWFFSG) under locked rotor fault scenarios and counter-rotating operational direction for fault withstand capability is investigated. The IDRWFFSG and the locked rotor fault scenarios are defined, and the magnetic path formation is explained. An integrated mathematical and electromagnetic modelling of the generator characteristics performance comprising torque quality, output power, efficiency and power factor are undertaken, based on the finite element method (FEM) under fault conditions. The electromagnetic characteristics are investigated independently for the inner and outer rotors under locked conditions while the counterpart rotor is rotated in both clockwise (CW) and counterclockwise (CCW) directions. The analysis confirms that CCW offers a comparatively better response than CW, with excellent locked rotor fault withstand capability. In the case of CCW operation, the average torque, output power, efficiency, and power factor are improved. Based on the results, it is determined that the rotational direction of the rotor is selected depending on the prerequisite demand of high efficiency, high power factor, and high output power when one of the rotors goes under a locked condition. Finally, a test prototype is developed to validate the predicted electromagnetic characteristics, of which the measured results confirm the effectiveness of the IDRWFFSG fault withstand capability study.